Let us say John has taken already X number of tests and his current average for the X tests taken is A.

If John gets a 97 on his next math test, his average will be 90.

So we can say;

`(AxxX+97)/(X+1) = 90`

`AxxX+97 = 90(X+1)`

`AxxX = 90(X+1)-97 ----(1)`

If he gets 73, his average will be 87.

Now we can say;

`(AxxX+73)/(X+1) = 87`

`AxxX+73 = 87(X+1)`

`AxxX = 87(X+1)-73 ----(2)`

(1) = (2)

`90(X+1)-97 = 87(X+1)-73`

`X = 21/3 `

`X = 7`

*So John has already taken 7 subjects.*

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now